Study the Structural Behaviour of Ferrocement Beam - Bong, J.H.L (Universiti Malaysia Sarawak (UNIMAS), 2010)
The need of the construction industry to look for a reliable and cheaper strengthening component for reinforced concrete structure has been lead to the usage of ferrocement which proves to be a promising solution. This paper describes the structural short-term behaviour of a beam strengthened with ferrocement laminate and identifies its advantages. beam which is strengthened with forrecement laminate is compared to a control beam for analysis of advantages of using ferrocement.